Adverse cutaneous drug reactions reporting in a tertiary care teaching hospital in Eastern India: a retrospective study - Bose, Manika; Misra, Debasish; Parida, Sansita; Das, Smita; Mishra, Swati; Mishra, Sudhansu S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Any unwanted changes to mucous membrane, skin, its appendages and drug eruptions related adverse events are known as adverse cutaneous drug reaction (ACDR). It has 2-5% incidence in developing countries. The current study was undertaken to analyse adverse cutaneous drug reactions spectrum clinically, drugs responsible, assessment of causality, severity, and preventability in our setup. Methods: Current study was an observational, retrospective, non-interventional analysis of voluntarily reported ADRs forms, between April 2018 and January 2020. All cutaneous ADRs reported within this period were identified. Data obtained were expressed in numbers, percentages. Results: 130 cutaneous ADRs was reported during the period of study. Fixed drug eruptions (30%) was the most common cutaneous reaction. The most common causal drug groups were antimicrobials (58.5%). Amongst antimicrobials, ornidazole (8.5%) was the most common drug. The most common drug in NSAID group was paracetamol (14.6%). The major drug causing ACDRs in our study was Paracetamol (14.6%). Assessment of causality revealed 37.7% were probable and 62.3% were possible reactions. Assessment of severity showed 78.5% as mild and 21.5% as moderate. Assessment of preventability showed that 6.1% probably preventable and 93.9% not preventable. Conclusions: Knowledge of the pattern of cutaneous reactions and the causative drugs guides us in early diagnosis of the condition, better management and associated decrease in morbidity, mortality. In the current study, the most common causal drug group were antimicrobials. The most common morphological pattern and drug causing ACDRs were fixed drug eruptions and paracetamol, respectively.